Performance, combustion and knock assessment of a high compression ratio and lean-burn heavy-duty spark-ignition engine fuelled with n-butane and liquefied methane gas blend. (1st September 2018) - Duan, Xiongbo; Liu, Jingping; Yao, Jun; Chen, Zheng; Wu, Cheng; Chen, Ceyuan; Dong, Hao
Abstract: An experimental investigation was conducted on the performance, combustion and knock characteristics of a high compression ratio, lean-burn heavy-duty spark ignition (SI) engine fuelled with n-butane and liquefied methane gas blend. Specifically, some technical adaptations were carried out on the original compression ignition (CI) engine for changing the direct fuel injection system into the electronic controlled intake port gas injection and implementing a high-energy ignition system. Results indicate that the in-cylinder pressure, heat release rate and cumulative heat release amount increase with the increased n-butane energy share. Once the n-butane energy ratio exceeds 5% in 1400 r/min, full-load, light knock occurs at this operating condition. In addition, the 50% burning location is advanced, the 10–90% combustion duration is shortened, and knocking intensity is strengthened. Furthermore, the maximum pressure rise rate fluctuates around the average value, and the oscillation amplitude also ascends with increased n-butane energy share which results in higher cycle-by-cycle variation. However, the IMEP and indicated thermal efficiency firstly go up with the increased percentage of the n-butane energy share and then decrease. Highlights: A comparative study of effects of LMG and n-butane blend on a high CR, lean-burn heavy-duty SI engine. IMEP and ITE can improve with the increasing percentage of n-butane energy ratio. The CCV increases with the n-butane energy share at lean mixture conditions. The knock of LMG and n-butane blend is more sensitive than the LMG.